Implementasi Prinsip-Prinsip Good Governance Guna Efektivitas Pelayanan Publik Pada Kantor Kelurahan Wonokromo Kota Surabaya - Adam Permana Putra; Maulidah Narastri (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to analyze the implementation of public services, the prevailing bureaucracy and the suitability of the computerized service system when viewed from the principles of good governance at the Wonokromo Kora Subdistrict Office, Surabaya. The research method used is a qualitative descriptive approach. The required research data collection was 6 informants consisting of 4 sub-district staff and 2 community recipients of public services. The data analysis techniques used are data collection, data triangulation, data reduction, and data presentation. The results of the research found that the Wonokromo Subdistrict Office, Surabaya City, in carrying out its services, has not fully implemented the principles of good governance, and reporting on public servants has not been fully transparent because it requires permission from the District first and certainty of when residents can collect files or the results of the service are sometimes not fully implemented.